2020
DOI: 10.1038/s41598-020-76878-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo O2 imaging in hepatic tissues by phosphorescence lifetime imaging microscopy using Ir(III) complexes as intracellular probes

Abstract: Phosphorescence lifetime imaging microscopy (PLIM) combined with an oxygen (O2)-sensitive luminescent probe allows for high-resolution O2 imaging of living tissues. Herein, we present phosphorescent Ir(III) complexes, (btp)2Ir(acac-DM) (Ir-1) and (btp-OH)3Ir (Ir-2), as useful O2 probes for PLIM measurement. These small-molecule probes were efficiently taken up into cultured cells and accumulated in specific organelles. Their excellent cell-permeable properties allowed for efficient staining of three-dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 59 publications
(77 reference statements)
1
34
0
Order By: Relevance
“…The question arose as to whether the enhanced green emission from ASb-2 in dead cells was due to low O 2 levels in dead cells. To examine this further, the molecular probe BTPDM1, which was developed as a versatile O 2 probe [46][47][48], was used to measure intracellular O 2 levels in dead cancer cells in the presence or absence of ASb-2. As shown in Figure 2J, a very weak red emission from BTPDM1 (3 µM) was observed before and after the treatment with ASb-2 (50 µM), suggesting that the enhanced emission from ASb-2 in dead Jurkat cells is not due to the low O 2 levels.…”
Section: 1mentioning
confidence: 99%
“…The question arose as to whether the enhanced green emission from ASb-2 in dead cells was due to low O 2 levels in dead cells. To examine this further, the molecular probe BTPDM1, which was developed as a versatile O 2 probe [46][47][48], was used to measure intracellular O 2 levels in dead cancer cells in the presence or absence of ASb-2. As shown in Figure 2J, a very weak red emission from BTPDM1 (3 µM) was observed before and after the treatment with ASb-2 (50 µM), suggesting that the enhanced emission from ASb-2 in dead Jurkat cells is not due to the low O 2 levels.…”
Section: 1mentioning
confidence: 99%
“…Iridium(III) complexes are the most promising probes for the evaluation of oxygen status in biological objects because of their photostability, readily tunable emission color, high quantum yields and relatively short emission lifetimes. A number of oxygen probes based on luminescent iridium(III) complexes have been developed [22,[27][28][29][30][31]. Amphiphilic polymers with chemically bonded phosphorescent iridium(III) complexes are attractive oxygen probes because the hydrophilic units of these polymers prevent the interaction of hydrophobic phosphorescent units with different biomolecules of the biological object and minimize the distortion of oxygen content evaluation.…”
Section: Biological Properties Of Polymers P1-p4mentioning
confidence: 99%
“…In the last decade, a number of iridium luminophores have been synthesized and their use as phosphorescent oxygen sensors in tumor cells and tissues has been demonstrated [22,[27][28][29]. Neutral and ionic deep red emitting iridium(III) complexes have been obtained recently and their applicability as oxygen-sensing probes in live cells and tissues was investigated in detail [30,31]. Meanwhile, the search for new sensors that are more suitable for biological applications is still in demand to meet the requirements of high water solubility, low toxicity, high phosphorescence quantum yield and strong dependence of phosphorescence signal on oxygen concentration in the physiological range.…”
Section: Introductionmentioning
confidence: 99%
“…For phosphorescence measurement, the mice were intravenously injected with 8.4 mg/kg BTPDM1 (Yoshihara et al , 2015 ) before imaging. It has been previously demonstrated that BTPDM1 distributes to most tissues in the body within 2 h after injection and accumulates in the cells of these tissues for at least 24 h. Furthermore, phosphorescence imaging using BTPDM1 determined that oxygen level in hypoxic tumors, renal cortex, and hepatic lobules in live animals ranged from 0.8 to 60 mmHg (Hirakawa et al , 2015 ; Yoshihara et al , 2015 ; Mizukami et al , 2020 ), showing that BTPDM1 has high sensitivity with a wide dynamic range. Phosphorescent and fluorescent and images were collected at a depth of 100–150 μm below the skull bone surface and detected through band‐pass emission filters at 450/50 nm (for NAD(P)H autofluorescence), 525/50 nm (for GFP and EGFP), and 620/60 nm (for tdTomato and BTPDM1).…”
Section: Methodsmentioning
confidence: 99%